Binary cyclic-gap constant weight codes with low-complexity encoding and decoding - Sasidharan, Birenjith; Viterbo, Emanuele; Dau, Son Hoang (Designs, codes, and cryptography, 2024)
In this paper, we focus on the design of binary constant weight codes that admit low-complexity encoding and decoding algorithms, and that have size M = 2 k so that codewords can conveniently be labeled with binary vectors of length k . For every integer ℓ ≥ 3 , we construct a ( n = 2 ℓ , M = 2 k ℓ , d = 2 ) constant weight code C [ ℓ ] of weight ℓ by encoding information in the gaps between successive 1’s of a vector, and call them as cyclic-gap constant weight codes. The code is associated with a finite integer sequence of length ℓ satisfying a constraint defined as anchor-decodability that is pivotal to ensure low complexity for encoding and decoding. The time complexity of the encoding algorithm is linear in the input size k , and that of the decoding algorithm is poly-logarithmic in the input size n , discounting the linear time spent on parsing the input. Both the algorithms do not require expensive computation of binomial coefficients, unlike the case in many existing schemes. Among codes generated by all anchor-decodable sequences, we show that C [ ℓ ] has the maximum size with k ℓ ≥ ℓ 2 - ℓ log 2 ℓ + log 2 ℓ - 0.279 ℓ - 0.721 . As k is upper bounded by ℓ 2 - ℓ log 2 ℓ + O ( ℓ ) information-theoretically, the code C [ ℓ ] is optimal in its size with respect to two higher order terms of ℓ . In particular, k ℓ meets the upper bound for ℓ = 3 and one-bit away for ℓ = 4 . On the other hand, we show that C [ ℓ ] is not unique in attaining k ℓ by constructing an alternate code C ^ [ ℓ ] again parameterized by an integer ℓ ≥ 3 with a different low-complexity decoder, yet having the same size 2 k ℓ when 3 ≤ ℓ ≤ 7 . Finally, we also derive new codes by modifying C [ ℓ ] that offer a wider range on blocklength and weight while retaining low complexity for encoding and decoding. For certain selected values of parameters, these modified codes too have an optimal k .